Structure Optimization Design for Brake Drum Based on Response Surface Methodology - Zheng, Bin; Wang, Xin; Zhang, Jingdong (Manufacturing Technology Journal, 2021)
Taking a brake drum as the research object, the dynamic characteristics analysis and optimization designare carried out by using the finite element method.In order to increase the stiffness without increasing weight of brake drum, the main design parameters were tested by Box-Behnken experiment design. The three-dimensional model of brake drum was established by using SolidWorks software, then the finite element model of brake drumwasobtainedby imported into ANSYS software and its modal analysis was carried out. On the basis of modal analysis, the three important dimensions of brake drum were defined as input parameters, the drum weight, the first, second and third natural frequencies are defined as output parameters. The response surface model between the input and output parameters was established by using DOE (Design of Experiment). Finally, the input parameters were optimized by multiobjective genetic algorithmand the fivePareto solutionswas obtained. The fifth solution was chosen as the optimal solutionbased on the production technique.The weight of brake drum was not changed obviously after optimization, but the first, second and thirdnatural frequencies were increased by13.07 %, 8.92 % and12.73 %respectively, which provided a new idea for the design and optimization for brake drum.
Keywords: Brake drum; Sensitivity analysis; Response surface model; Multiobjective optimization; Finite element analysis; Design of experiment